Influence of Massage and Skin Hydration on Dermal Penetration Efficacy of Nile Red from Petroleum Jelly-An Unexpected Outcome - Vasudha Kaushik; Yameera Ganashalingam; Robert Schesny; Christian Raab; Soma Sengupta; Cornelia M. Keck (MDPI AG, 2021)
The study aimed at comparing the influence of direct and indirect skin hydration as well as massage on the dermal penetration efficacy of active compounds. Nile red was used as a lipophilic drug surrogate and was incorporated into Vaseline (petroleum jelly). The formulation was applied with and without massage onto either dry skin or pre-hydrated, moist skin. It was expected that the occlusive properties of Vaseline in combination with massage and enhanced skin hydration would cause a superposition of penetration-enhancing effects, which should lead to a tremendous increase in the dermal penetration efficacy of the lipophilic drug surrogate. Results obtained were diametral to the expectations, and various reasons were identified for causing the effect observed. Firstly, it was found that Vaseline undergoes syneresis after topical application. The expulsed mineral oil forms a film on top of the skin, and parts of it penetrate into the skin. The lipophilic drug surrogate, which is dissolved in the mineral oil, enters the skin with the mineral oil, i.e., via a solvent drag mechanism. Secondly, it was found that massage squeezes the skin and causes the expulsion of water from deeper layers of the SC. The expulsed water can act as a water barrier that prevents the penetration of lipophilic compounds and promotes the penetration of hydrophilic compounds. Based on the data, it is concluded that dermal penetration is a complex process that cannot only be explained by Fick's law. It is composed of at least three different mechanisms. The first mechanism is the penetration of active ingredients with their solvents into the skin (convection, solvent drag), the second mechanism is the penetration of the active ingredient via passive diffusion, and the third mechanism can involve local penetration phenomena, e.g., the formation of liquid menisci and particle-associated penetration enhancement, which occur upon the evaporation of water and/or other ingredients from the formulation on top of the skin.